MRI Evaluation of the Contralateral Breast in Women with Recently Diagnosed Breast Cancer: 2-Year Follow-up. Issue 1 (8th November 2019) - Debruhl, Nanette D; Lee, Su-Ju; Mahoney, Mary C; Hanna, Lucy; Tuite, Catherine; Gatsonis, Constantine A; Lehman, Constance
Abstract: Objective: The American College of Radiology Imaging Network Trial 6667 showed that MRI can detect cancer in the contralateral breast that is missed by mammography and clinical examination at the time of the initial breast cancer diagnosis, based on 1-year follow-up. This study is a continuation of the trial that evaluates the diagnostic accuracy of MRI for contralateral breast cancer after 2 years of follow-up. Methods: In total, 969 women with a diagnosis of unilateral breast cancer and no clinical or imaging abnormalities in the contralateral breast underwent breast MRI. The cancer status of all participants was monitored for 2 years after the initial MRI. Follow-up included documentation of any clinical, imaging, or interventional procedures performed. A study participant was considered positive for cancer if she had a tissue diagnosis of in situ or invasive breast cancer in the contralateral breast within 730 days of her initial MRI. Results: Three additional cancers were diagnosed in the study population in the second year of the trial. The diagnostic yield for MRI for the 2-year period was 3% (31/969). After 2 years of follow-up, breast MRI has a sensitivity of 86% and specificity of 88% for detection of contralateral breast cancer. Its negative predictive value was 99%, and its positive predictive value was 22%. These values did not change significantly from the 1-year data. Conclusion: A negative contralateral breast MRI has a very high and reliable negative predictive value over 2 years, and, therefore, is helpful in managing and counseling patients during the period of initial diagnosis and early treatment.